The local community: an entity discriminated against in spatial decision-making in Poland? - Bednarek-Szczepańska, Maria (Bulletin of Geography. Socio-economic Series, 2020)
The article concerns the legal dimension of local communities’ participation in selected aspects of shaping space in Poland. The results of the review of legal regulations are presented, including interpretations of regulations made by other authors. Examples taken from previous research were used to show the functioning of these regulations in practice and their consequences. The aim of the article is to assess the legal conditions for the participation of local communities in spatial planning, planning of protected areas and location of investments in Poland, in relation to selected theoretical concepts, as well as to assess the consequences of these conditions. In the legal dimension, the participation of the local community in shaping space is symbolic, in the terminology of the Arnstein ladder. The dominant model is a non-binding opinion on ready-made projects and plans, instead of collaboration in their creation.